Tanfidz Wasait Bithoqotuz Zaujaini Liziyadati Nasyatu Wa Nataiju Thulabus Shaful Khamis Limadatil Arabiyati Fil Madrasatil Ibtidaiyatil Muhammadiyati Bluran, Lijawal Wustha - Nur Aini Khasanah, Isna; Islam, Saiful; Qosim, Muhammad Nanang; Kholiq Hasan, Moh. Abdul (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2023)
بناء على مشكلات التعلم ، فإن أهداف الدراسة: 1) زيادة النشاط التعليمي لطلاب الصف الخامس باستخدام وسائط بطاقة الزوجين في مادة اللغة العربية. 2) لتحسين نتيجة طلاب الصف الخامس باستخدام وسائط بطاقة الزوجين في مادة اللغة العربية.نتائج هذه الدراسة كالتالي: 1) تنفيذ وسائط بطاقة الزوجين في مادة تعلم اللغة العربية للصف الخامس قادر على زيادة النشاط في التعلم ، حيث بلغ الدليل في الدورة الأولى من نشاط الطالب 85٪ 27 طالبًا. في الحلقة الثانية بلغ نشاط الطلاب 94٪ من 27 طالبًا. 2) تنفيذ وسائط بطاقة الزوجين في مادة تعلم اللغة العربية للصف الخامس قادر على تحسين متوسط نتائج التعلم ، مع وجود دليل في الحلقة الأولى على أن درجة الطلاب وصلت إلى 78٪ بمتوسط 6.0 درجات. 27 طالبًا. في الحلقة الثانية ، وصلت درجات الطلاب إلى 96٪ بمتوسط 8.4 من أصل 27 طالبًا.بناء على نتائج البحث الذي تم إجراؤه ، يود الباحث تقديم اقتراحات على النحو التالي: 1) للطلاب يوصى بالاهتمام بالدروس التي شرحها المعلم وأن يكونوا نشيطين في عملية التعلم. 2) للمعلمين لاستخدام وتطبيق الوسائط الزوجية في تعلم مواد اللغة العربية. 3) للباحثين التاليين لجعل هذا البحث يعطي فوائد ويصبح مرجعا لأبحاثهم Based on the learning problems above, the objectives of study: 1) to increase the learning activeness of class 5 students by using the couple card media in Arabic language subject at MI Muhammadiyah Bloran. 2) to improve the result of class 5 students by using the couple card media in Arabic language subject at MI Muhammadiyah Bloran.The results of this study are as follows: 1) Implementation of the couple card media in learning Arabic language subject for class 5 at MI Muhammadiyah Bloran is able to increase activeness in learning, with evidence in the first cycle of student activeness reaching 85% of 27 students. In the second cycle, student activeness reached 94% of 27 students. 2) Implementation of the couple card media in learning Arabic language subject for class 5 at MI Muhammadiyah Bloran is able to improve the average in learning outcomes, with evidence in the first cycle that the students score reached 78% with an average score of 6.0 out of 27 students. In the second cycle, the students' scores reached 96% with an average score of 8.4 out of 27 students.Based on the research results conducted, the researcher would like to provide suggestions as follows 1) for students it is recommended to pay attention to the lessons explained by the teacher and be active in the learning process. 2) for teachers to utilize and apply the couple card media in learning Arabic language subjects. 3) for the following researchers to make this give benefits research and become a reference for their researchs Berdasarkan pada permasalahan pembelajaran yang telah disebutkan, maka tujuan dari penelitian ini ialah: 1) untuk meningkatkan keaktifan belajar siswa kelas 5 dengan menggunakan media couple card dalam pelajaran bahasa Arab MI Muhammadiyah Bloran. 2) untuk meningkatkan hasil belajar siswa kelas 5 dengan menggunakan media couple card dalam pelajaran Bahasa arab MI Muhammadiyah Bloran.Hasil dari penelitian ini adalah sebagai berikut: 1) Bahwa penerapan media couple card dalam pembelajaran bahasa Arab kelas 5 MI Muhammadiyah Bloran dapat meningkatkan keaktifan dalam pembelajaran, dengan bukti dalam siklus pertama keaktifan siswa mencapai 85% dari 27 siswa. Pada siklus kedua keaktifan siswa mencapai 94% dari 27 siswa. 2) Bahwa penerapan media couple card dalam pembelajaran Bahasa arab kelas 5 MI Muhammadiyah Bloran dapat meningkatkan hasil belajar dalam pembelajaran, dengan bukti dalam siklus pertama nilai siswa mencapai presentase nilai 78% dengan nilai rata-rata 6,0 dari 27 siswa. Pada siklus kedua nilai siswa mencapai presentase nilai 96% dengan nilai rata-rata 8,4 dari 27 siswa.Berdasarkan hasil dari penelitian yang dilakukan oleh peneliti, peneliti ingin memberikan saran diantaranya: 1) untuk siswa dianjurkan untuk memperhatikan pelajaran yang dijelaskan oleh guru dan aktif dalam proses pembelajaran. 2) untuk guru agar dapat memanfaatkan dan menerapkan media couple card dalam pembelajaran bahasa Arab. 3) untuk peneliti selanjutnya agar menjadikan penelitian ini bermanfaat dan menjadi referensi untuk penelitiannya